2016
DOI: 10.1016/j.neuroimage.2015.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of cortico-cerebellar functional connectivity after motor learning

Abstract: Interactions between the cerebellum and primary motor cortex are crucial for the acquisition of new motor skills. Recent neuroimaging studies indicate that learning motor skills is associated with subsequent modulation of resting-state functional connectivity in the cerebellar and cerebral cortices. The neuronal processes underlying the motor-learning induced plasticity are not well understood. Here, we investigate changes in functional connectivity in source-reconstructed electroencephalography (EEG) followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 80 publications
(103 reference statements)
10
36
0
2
Order By: Relevance
“…Expertise effects in motor learning were also revealed in alpha power-BOLD correlations between motor regions and cerebellum. Recently, Mehrkanoon et al [2016] used a motor learning task with EEG to perform a functional connectivity analysis on cortical sources. They showed that increases in functional connectivity between motor regions and cerebellum in the alpha band after motor learning.…”
Section: Group Differences In Motor Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Expertise effects in motor learning were also revealed in alpha power-BOLD correlations between motor regions and cerebellum. Recently, Mehrkanoon et al [2016] used a motor learning task with EEG to perform a functional connectivity analysis on cortical sources. They showed that increases in functional connectivity between motor regions and cerebellum in the alpha band after motor learning.…”
Section: Group Differences In Motor Learningmentioning
confidence: 99%
“…As an example, baseball players are exceedingly good at deciding whether to swing at a pitch, given a split second to observe a baseball's trajectory, spin, and speed. During this split second decision, there is little time for explicit decision-making; instead, the ability to hit a baseball relies on largely implicit mechanis ms that must link perception to action as a fast perceptual decision (Muraskin, et al, in press; Muraskin, et al, 2015; Nakamoto and Mori, 2008; Radlo, et al, 2001). This process is largely dependent on the efficiency of globally distributed networks throughout the brain (Forstmann, et al, 2010; Heekeren, et al, 2004); however, precisely which functional and structural components of these networks foster expert level performance remains a mystery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in strength in the fronto-parietal network and the cerebellum network after 11 minutes of motor learning have also been detected 36 . This is further supported by EEG evidence showing increased resting-state connectivity within the cerebellum and between the cerebellum and motor cortex, after training in a force task 37 .…”
Section: Discussionmentioning
confidence: 58%
“…Accordingly, Bigdely-Shamlo et al showed that it might be beneficial to additionally consider 3D dipole locations for clustering, which result from a source reconstruction step [22]. We agree on this view, as specifically from a clinical perspective knowledge about functional brain regions could provide added value [43]. However, source reconstruction comes at a price, as results are sensitive to initial assumptions and raw signal quality, among others [44].…”
Section: Discussionmentioning
confidence: 60%